Alienusolin, a New 4α-Deoxyphorbol Ester Derivative, and Crotonimide C, a New Glutarimide Alkaloid from the Kenyan Croton alienus - Ndunda, Beth; Langat, Moses K.; Wanjohi, John M.; Midiwo, Jacob O.; Kerubo, Leonidah O. (Planta Medica, 2013)
Two novel compounds, alienusolin, a 4α-deoxyphorbol ester (1), crotonimide C, a glutarimide alkaloid derivative (2), and ten known compounds, julocrotine (3), crotepoxide (4), monodeacetyl crotepoxide (5), dideacetylcrotepoxide, (6), β-senepoxide (7), α-senepoxide (8), (+)-(2S,3R-diacetoxy-1-benzoyloxymethylenecyclohex-4,6-diene (9), benzyl benzoate (10), acetyl aleuritolic (11), and 24-ethylcholesta-4,22-dien-3-one (12) were isolated from the Kenyan Croton alienus. The structures of the compounds were determined using NMR, GCMS, and HRESIMS studies.
Keywords: 4α-deoxyphorbol ester; glutarimide alkaloid; Croton alienus; Euphorbiaceae